2016
DOI: 10.1024/0301-1526/a000534
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction after ultrasoundguided foam sclerotherapy for varicose veins - a case report and review of the literature of a rare but serious adverse event

Abstract: Key message: The possibility of potentially serious cardiac complications after sclerotherapy for varicose veins has to be kept in mind. Chest symptoms lasting longer than 5 minutes or with typical features of acute coronary syndrome have to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…20 A feeling of chest pressure or tightness has been reported after sclerotherapy, and it is usually rapidly resolved. 21 In a large prospective cohort study, chest pressure was reported in 1.1% in patients treated with UGCDFS. 22 According to Morrison et al., 23 chest tightness was more frequent when large foam volumes (>15 ml) were injected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 A feeling of chest pressure or tightness has been reported after sclerotherapy, and it is usually rapidly resolved. 21 In a large prospective cohort study, chest pressure was reported in 1.1% in patients treated with UGCDFS. 22 According to Morrison et al., 23 chest tightness was more frequent when large foam volumes (>15 ml) were injected.…”
Section: Discussionmentioning
confidence: 99%
“…24 In our study, the average volume of foam sclerosant was 12 ml (range, 10-15 ml), and chest pressure for a few seconds after procedure was seen in 1.3% of patients. Engelberger et al 21 reported a case in which they used 12 ml of 1% polidocanol foam where a 78year-old patient had a heart attack following UGCDFS. In our study, the average age in group 1 was 69.6 AE 4.5 (65-89), and chest pressure was not associated with cardiac symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Further cases have been reported of myocardial infarction after foam sclerotherapy with aethoxysklerol or sodium tetradecylsulphate. [9][10][11] The difficulty of assessing these latter cases as to whether they constitute a reaction to the sclerosant or the gas bubbles in the foam is the inconsistency of reporting which detergent was used and in what concentration, what gas was used to make the foam and the total dose injected into which veins.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of cardiac arrest in children where high doses of aethoxysklerol were injected into venous malformations also seem to point towards a direct cardiotoxicity of the drug, 6,7 as does a report of a 48-year-old lady who underwent cardiac arrest following the injection of '7-mL foam polidocanol injection'. 8 Polidocanol foam sclerotherapy has also been reported to cause myocardial infarction in a 78-year-old patient, 9 but myocardial infarction with foam sclerotherapy has been reported with foam made from both aethoxysklerol and sodium tetradecyl sulphate. 10,11 Further cases have been reported of myocardial infarction after foam sclerotherapy with aethoxysklerol or sodium tetradecylsulphate.…”
Section: Discussionmentioning
confidence: 99%